First Centennial of Feminicide in the Women’s March and Farm Worker’s Strike for salary improvements in Huacho - Smith Bisso, Alejandro (2017)
In this story we present the panorama of the political time in which the first femicide of the history of social struggles in Peru occurred, one hundred years ago, in 1917, highlighting the figure of Irene Salvador Grados as first martyr leader, in addition to mentioning to the other fallen women. This event is part of the process of recognising of the right to eight hours work shift signed in 1916, in Huacho. It reflects  on the political forces that allowed the events.